2006
DOI: 10.1016/j.physletb.2006.10.026
|View full text |Cite
|
Sign up to set email alerts
|

g factors of 31,32,33Al: Indication for intruder configurations in the 33Al ground state

Abstract: The g factors of 31,32,33 Al have been measured using the β-nuclear magnetic resonance (β-NMR) technique on spin-polarized beams produced in the fragmentation of a 36 S (77.5 MeV/u) beam on a 9 Be target. Nearly pure beams of Al (Z = 13) isotopes were selected with the highresolution fragment separator LISE at GANIL. An asymmetry as high as 6% has been observed in the β-NMR curve for 32 Al implanted in a Si single crystal. The magnetic moment of the N = 20 nucleus 33 Al is obtained for the first time: μ( 33 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 33 publications
3
44
1
Order By: Relevance
“…This is inconsistent with a picture in which no particle-hole excitations occur: for a closed-shell isotope like 33 Al 20 the quadrupole moment should decrease with respect to the open-neutron shell isotopes 27,31 Al. That is illustrated in the shell model calculations using the USD shell model interaction [28] with a 16 O core and protons and neutrons restricted to the sd-shell model space, the triangles in Fig. 2.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…This is inconsistent with a picture in which no particle-hole excitations occur: for a closed-shell isotope like 33 Al 20 the quadrupole moment should decrease with respect to the open-neutron shell isotopes 27,31 Al. That is illustrated in the shell model calculations using the USD shell model interaction [28] with a 16 O core and protons and neutrons restricted to the sd-shell model space, the triangles in Fig. 2.…”
Section: Resultsmentioning
confidence: 96%
“…2. The ANTOINE shell model code has been used with SDPF-U-MIX [29], the most recent effective interaction for this region, which builds upon a 16 O core and comprises the full sd and pf shell for neutrons. This allows excitations of neutrons across N = 20 and mixing between np-nh configurations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclei like 34,35 Al are lying at the boundary of this 'Island of Inversion'. Little experimental information about their ground state configurations are available in literature [7][8][9]. g-factor measurement of 34 Al by Himpe et al [7] showed the need of intruder components in 34 Al wave function to account for the observed large magnetic moment.…”
Section: Introductionmentioning
confidence: 99%
“…Little experimental information about their ground state configurations are available in literature [7][8][9]. g-factor measurement of 34 Al by Himpe et al [7] showed the need of intruder components in 34 Al wave function to account for the observed large magnetic moment. Recently, an experiment (S306) has been performed [5] at GSI, Darmstadt using LAND-FRS setup [10] to explore the neutron-rich exotic nuclei in and around N ∼ 20 'Island of Inversion' (Fig.…”
Section: Introductionmentioning
confidence: 99%